please help
Given the functions k(x) = 2x2 − 7 and p(x) = x − 4, find (k ∘ p)(x).

(k ∘ p)(x) = 2x2 − 8x + 16
(k ∘ p)(x) = 2x2 − 16x + 32
(k ∘ p)(x) = 2x2 − 16x + 25
(k ∘ p)(x) = 2x2 − 11

Respuesta :

Answer:

(k ∘ p)(x) = 2x²-16x+25

Step-by-step explanation:

(k ∘ p)(x) = 2(x-4)²-7

(k ∘ p)(x) = 2(x²-8x+16)-7

(k ∘ p)(x) = 2x²-16x+32-7

(k ∘ p)(x) = 2x²-16x+25

The value of (k ∘ p)(x) is [tex]2x^2-16x+25[/tex]

Given information:

The functions are [tex]k(x) = 2x^2 - 7[/tex] and p(x) = x − 4

Calculation of the value:

[tex]= 2(x-4)^2-7\\\\= 2(x^2-8x+16)-7\\\\= 2x^2-16x+32-7\\\\= 2x^2-16x+25\\\\[/tex]

Learn more about the function here: https://brainly.com/question/19293043